Strip Intercropping of Rye–Vetch Mixtures: Effects on Weed Growth and Competition in Strip-tilled Sweet Corn. Issue 1 (24th January 2019) - Lowry, Carolyn J.; Brainard, Daniel C.
Abstract: Strip-intercropping of functionally diverse cover crop mixtures including cereal rye ( Secale cereale L.) and hairy vetch ( Vicia villosa Roth) is one mechanism by which nitrogen (N) banding can be applied to an organic, strip-tilled system to increase crop competitiveness over weeds. We hypothesized that by targeting hairy vetch, a low C:N legume, to the tilled strip directly in row with future crop establishment, and cereal rye, a high C:N grass, to the untilled strip directly between future crop rows, that N would be preferentially available to the crop. We conducted a field study between 2011 to 2013 in southwest Michigan to examine the effects of rye–vetch mixture spatial arrangement (strip intercropping vs. full-width mixture) on (1) soil inorganic N; (2) weed biomass; and (3) sweet corn ( Zea mays L.) biomass, yield, and competitiveness against weeds. We found that as the proportion of vetch biomass in the crop row (in-row, IR) increased, we also saw increasing levels of IR soil inorganic N and greater early sweet corn N uptake and growth relative to weeds. However, sweet corn yield and final biomass were more responsive to vetch biomass across the whole plot (WP) and did not respond to rye and vetch segregation into strips. Increasing vetch WP biomass increased sweet corn final biomass across both years, but only increased corn competitiveness against weeds in 1 out of 2 years and decreased sweet corn competitiveness in the other year. Strip-intercropping of cereal rye and hairy vetch has potential to increase soil N availability to the crop, thereby increasing early crop competitiveness, which may lower weed management costs.